(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The present work describes briefly the results of the synthesis and investigation of physicochemical properties and structures of coordination compounds of metals with amines (ortho-, meta-, para-aminopyridines and methyl derivatives of ortho-aminopyridine), amides of pyridine acids (ortho-, meta-, para-isomers and their derivatives), hydrazides and hydrazone amine pyridine carboxylic acids and other acids. The structures of the compounds synthesized were determined with x-ray crystallography, spectroscopy (IR, Raman, electronic) and other physicochemical methods. The results of biological investigations of some of the compounds are also given.